129k views
3 votes
Consider the following graph of two functions.(8-1-2)Step 3 of 4: Find (8.5(-2)Enable Zoom/Pan866) = -3010-35SG) = x + 3

Consider the following graph of two functions.(8-1-2)Step 3 of 4: Find (8.5(-2)Enable-example-1
User Anwardo
by
5.1k points

1 Answer

2 votes

The question requires that we evaluate the value of:


(g\cdot f)(-2)

Recall that:


\left(g\cdot \:f\right)\left(x\right)=g\left(x\right)\cdot \:f\left(x\right)

Therefore, we have that:


\left(g\cdot\:f\right)\left(-2\right)=g\left(-2\right)\cdot\:f\left(-2\right)

We can get the values of g(-2) and f(-2) from the graph as shown below:

Therefore, we have:


\begin{gathered} g(-2)=5 \\ f(-2)=1 \end{gathered}

Hence, we can calculate the composite function to be:


\begin{gathered} (g\cdot f)(-2)=5*1 \\ (g\cdot f)(-2)=5 \end{gathered}

Consider the following graph of two functions.(8-1-2)Step 3 of 4: Find (8.5(-2)Enable-example-1
User Joachim Schork
by
5.6k points